2023
DOI: 10.1101/2023.05.23.23290429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of age at menarche and menopause, reproductive lifespan, and stroke among Chinese women: Results from a national cohort study

Lu Chen,
Zhen Hu,
Xin Wang
et al.

Abstract: Background: The association between age of menarche, age of menopause, reproductive lifespan and risk of stroke in Chinese women remains unclear and requires further clarification.<break><break>Methods: A stratified multi-stage random sampling method was used to select participants at baseline in 2012-2015. The participants? basic information was collected through a standardized questionnaire by professional investigator and examined by trained medical personnel. Follow-up was completed in 2019 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Cisgender women have a lower risk of cardiovascular and cerebrovascular disease compared to cisgender men up until menopause, at which point their risk significantly increases (Hayward et al, 2000;Aggarwal et al, 2018). Earlier menarche and longer reproductive lifespan are also associated with lower risk of stroke, suggesting a beneficial influence of lifetime exposure to oestrogen on the cerebrovascular system [Chen et al, 2023; relatedly, lifetime oestrogen exposure also shows associations with better memory score and larger medial temporal cortical volumes (Steventon et al, 2023)]. Animal models demonstrate that 10.3389/fnhum.2023.1303871 oestrogen increases vasodilation (Tostes et al, 2003), decreases pathological vasoreactivity (Wassmann et al, 2001), and increases CBF and angiogenesis (Robison et al, 2019).…”
Section: Oestrogen and Progesteronementioning
confidence: 99%
See 1 more Smart Citation
“…Cisgender women have a lower risk of cardiovascular and cerebrovascular disease compared to cisgender men up until menopause, at which point their risk significantly increases (Hayward et al, 2000;Aggarwal et al, 2018). Earlier menarche and longer reproductive lifespan are also associated with lower risk of stroke, suggesting a beneficial influence of lifetime exposure to oestrogen on the cerebrovascular system [Chen et al, 2023; relatedly, lifetime oestrogen exposure also shows associations with better memory score and larger medial temporal cortical volumes (Steventon et al, 2023)]. Animal models demonstrate that 10.3389/fnhum.2023.1303871 oestrogen increases vasodilation (Tostes et al, 2003), decreases pathological vasoreactivity (Wassmann et al, 2001), and increases CBF and angiogenesis (Robison et al, 2019).…”
Section: Oestrogen and Progesteronementioning
confidence: 99%
“…While some studies report reduced CBF and CVR following menopause, high-quality evidence and consistent menopausal criteria are lacking (Ruediger et al, 2021). A confounding factor is the impact of age and physical fitness at menopause age on cerebrovascular health (Chen et al, 2023;Moir et al, 2023;Ruediger et al, 2023). A recent systematic review of the influence of sex hormones on cerebrovascular function in human subjects suggested that, though there were often differences between high and low hormonal states, the directions were not consistent (Skinner et al, 2021).…”
Section: Oestrogen and Progesteronementioning
confidence: 99%